Efficacy of a fipronil bait in reducing the number of fleas (Oropsylla spp.) infesting wild black‐tailed prairie dogs. Issue 1 (June 2017) - Poché, David M.; Hartman, Daniel; Polyakova, Larisa; Poché, Richard M.
ABSTRACT: Bubonic plague ( Yersinia pestis ) is a deadly zoonosis with black‐tailed prairie dogs ( Cynomys ludovicianus ) as a reservoir host in the United States. Systemic insecticides are a promising means of controlling the vectors, Oropsylla spp. fleas, infesting these prairie dogs, subsequently disrupting the Y. pestis cycle. The objective of this study was to conduct a field trial evaluating the efficacy of a grain rodent bait containing fipronil (0.005%) against fleas infesting prairie dogs. The study was performed in Larimer County, CO, where bait was applied to a treatment area containing a dense prairie dog population, three times over a three‐week period. Prairie dogs were captured and combed for fleas during four study periods (pre‐, mid‐, 1 st post‐, and 2 nd post‐treatment). Results indicated the use of bait containing fipronil significantly reduced flea burden. The bait containing fipronil was determined to reduce the mean number of fleas per prairie dog >95% for a minimum of 52 days post‐initial treatment application and 31 days post‐final treatment application. These results suggest the potential for this form of treatment to reduce flea population density on prairie dogs, and subsequently plague transmission, among mammalian hosts across the United States and beyond.